NATIONAL VALUES OF CENTRAL ASIAN PEOPLE IN RESOLVING FAMILY DISPUTES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study explores how national values embedded in the cultural, spiritual, and historical fabric of Central Asian societies inform the resolution of family disputes. Unlike Western paradigms that emphasize individual rights, Central Asian traditions prioritize collective well-being, familial integrity, and community harmony. The research highlights the roles of elders, community leaders, and informal legal institutions—such as local councils and shalish—in mediating conflicts related to marriage, inheritance, and generational tensions. Emphasis is placed on the communal decision-making process, respect for elders, and the influence of Islamic principles and customary law. Drawing on interdisciplinary perspectives, the study also examines the interplay between traditional values and contemporary legal frameworks. It argues that effective dispute resolution in Central Asia relies on the integration of indigenous practices with evolving legal norms, ensuring culturally grounded and socially sustainable outcomes. The findings underscore the importance of national values in fostering restorative justice, social cohesion, and resilience within family structures amid modernization and globalization pressures.